845 Assessing How Effectively Ankle Fractures Are Managed in Accordance with the BOAST Guidelines at a Major Trauma Centre. (19th August 2022) - Jobson, J; Saad, A; Fernandes, R; Jaly, I; Burahee, A
Abstract: Aim: Ankle fractures constitute approximately 10.2% of all bony injuries. Due to pressures exerted by the COVID-19 pandemic, a series of modifications have evolved within subspecialty fracture management. The aim of our study was to evaluate our adaptations to the COVID-19 pandemic and assess our management of ankle fractures according to the BOAST guidelines. Method: We performed a retrospective review of 30 skeletally mature patients with a closed ankle fracture presenting to a major tertiary centre. Our inclusion criteria comprised of the 'BOAST guidelines for ankle fracture management' published in 2016. Results: Of the 30 patients within our cohort, 40% (n= 12) had stable ankle fractures, whereas 60% (n= 18) were unstable (based on the weber classification and evidence of syndesmotic instability). 63% (n= 10) had fracture manipulations prior to surgery. 50% (n= 5) had a documented re-examination of neurovascular status. All patients had a post reduction image. 88% (n= 16) with unstable fractures underwent operative fixation. 6 patients underwent external fixation prior to definitive management. The average time from injury to definitive fixation was 12 days with a range from 0–22 days. Only 8 patients had clear documentation of intraoperative syndesmotic stability. Conclusions: The BOAST guidelines outline a range of standards that should be utilised when treating ankle fracture patients. We intend to use our study to educate healthcare professionals on the importance of accurate documentation and encourage shorter operative waiting times to improve standard of care and patient outcomes.